Plastic Waste Management in Bac Ninh Province: Current Status and Policy Implications - Anh, Ngo The; Giang, Nguyen Thi Huong; Viet, Nguyen Quoc (VNU Journal of Science: Earth and Environmental Sciences; Article in press, 2026)
Plastic waste has become a major environmental pressure in rapidly urbanizing and industrialized provinces of Vietnam. This study assesses the generation, composition, and spatial distribution of single-use plastics and non-biodegradable plastic bags in Bac Ninh Province through a large household, retail, and office survey (3,200 households and 400 establishments) and a waste audit of 675 samples. Average generation reached 17.14 kg/person/year (≈23.5 thousand tons/year), with strong variation across administrative units. Industrial–urban areas such as Yen Phong, Tien Du, Tu Son, and Bac Ninh City recorded the highest loads and densities, while rural districts generated markedly less. Plastic bottles represented 39% of household plastic waste by mass, followed by plastic bags (24%), reflecting both the recycling potential of rigid plastics and the leakage risks of lightweight items. Survey findings show a clear perception–behavior gap: although over 70% of respondents acknowledged environmental and health risks, fewer than 20% frequently practiced reduction behaviors. Spatial analysis identifies distinct hotspots where population, commerce, and industrial zones coincide with high waste loads. These results indicate that plastic management should prioritize differentiated interventions tailored to both geographic hotspots and specific waste composition (e.g., focusing on recovery for high-mass items and leakage reduction for lightweight items), integrating economic instruments (plastic bag levy, deposit–return schemes, strengthened Extended Producer Responsibility) with targeted communication and improved access to alternatives, supporting provincial and national plastic reduction strategies.